Transnational Chicanx perspectives on Ana Castillo - Hernández, Bernadine Marie; Roybal, Karen R. (Pittsburgh, Pa. : University of Pittsburgh Press, 2021)
Transnational Chicanx Perspectives on Ana Castillo is the first edited collection that focuses on Castillo's oeuvre, which directly confronts what happens in response to cultural displacement, mixing, and border crossing. Divided into five sections, this collection thinks about Castillo's poetics, language, and form, as well as thematic issues such as borders, immigration, gender, sexuality, and transnational feminism.
"For more than forty years, Chicana author Ana Castillo has produced novels, poems, and critical essays that forge connections between generations; challenge borders around race, gender, and sexuality; and critically engage transnational issues of space, identity, and belonging. Her contributions to Latinx cultural production and to Chicana feminist thought have transcended and contributed to feminist praxis, ethnic literature, and border studies throughout the Americas. Transnational Chicanx Perspectives on Ana Castillo is the first edited collection that focuses on Castillo's oeuvre, which directly confronts what happens in response to cultural displacement, mixing, and border crossing. Divided into five sections, this collection thinks about Castillo's poetics, language, and form, as well as thematic issues such as borders, immigration, gender, sexuality, and transnational feminism. From her first political poetry, Otro Canto, published in 1977, to her mainstream novels such as The Mixquiahuala Letters, So Far From God, and The Guardians, this collection aims to unravel how Castillo's writing impacts people of color around the globe and works in solidarity with other third world feminisms." --
Foreword / Frederick Luis Aldama -- Introduction / Karen R. Roybal and Bernadine M. Hernández -- Part I. The Chicanx letters. Lettered encounters / Ximena Keogh Serrano -- For the pleasure of the Chicanx poet / Shanna M. Salinas -- Unbounded and limitless / Olga L. Herrera -- Part II. So far from nation. -- "¿A'ca'o qué, comadre?" / Ayendy Bonifacio -- Identity formation and dislocation / Tereza M. Szeghi -- Selling the "authentic" / Electra Gamón Fielding -- So far from nation / Amelia María de la Luz Montes -- Part III. Give it to the globe. -- Queering space in Ana Castillo's Give it to me / Daniel Shank Cruz -- Queer(ing) motherhood in Ana Castillo's Black dove: Mamá, Mi'jo, and me / Elena Avilés -- Nostalgia for a future / Liliana C. González -- Giving it to the globe / Emma Pérez -- Part IV. Mamá, mijxs, and me. -- Priestess y pastora / Laura Elena Belmonte -- The unbreakable link / Rebecca A. Kennedy de Lorenzini -- Feminist imaginaries of justice / Araceli Esparza -- Chicana feminist literary subjectivity in a transnational frame / Ellie D. Hernández -- Part V. Teaching and pedagogy. -- Replanting you as winyan, uarhiti, kwe / Gabriela Spears-Rico -- Teaching Ana Castillo / Leigh Johnson -- "Never stay silent" / Sandra Ruiz -- Teaching Chicana literature in community college / Danizete Martínez -- Chapter -- 20. Por todos lados / Norma E. Cantú -- Part VI. An interview with Ana Castillo. -- An interview with Ana Castillo / Francisco J. Galarte -- Conclusion. Latinx/Chicanx feminist futures / Karen R. Roybal and Bernadine M. Hernández.
Online resource; title from PDF title page (JSTOR platform, viewed July 31, 2023).
JSTOR
Keywords: Castillo, Ana -- Criticism and interpretation; Castillo, Ana; Transnationalism in literature; Feminist literature -- History and criticism; Hispanic Americans in literature; Mexican Americans in literature; American literature -- Hispanic American authors -- History and criticism; Transnationalisme dans la littérature.; Féminisme -- Documentation -- Histoire et critique; Américains d'origine latino-américaine dans la littérature.; Américains d'origine mexicaine dans la littérature.; Littérature américaine -- Auteurs américains d'origine latino-américaine -- Histoire et critique; Transnationalism in literature; Mexican Americans in literature; Hispanic Americans in literature; Feminist literature; American literature -- Hispanic American authors; Criticism, interpretation, etc; Literary criticism; Critiques littéraires.